PARTISIPASI MASYARAKAT DAN ORANG TUA DALAM MENINGKATKAN MUTU PENDIDIKAN - Farikha, Farikha; Wahyudi, Wahyudi; Chiar, Muhammad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe focus of this research is the participation of the community and parents in improving the quality of education (TK Idhata 1, Banjar Village, Benua Kayong District, Ketapang Regency) with research questions directed at: How perceptions, planning, implementation, impact, evaluation, obstacles and solutions for community and parent participation in improving the quality of education in kindergarten Idhata 1, Banjar Village, Benua Kayong District, Ketapang Regency. To express these questions researchers used a qualitative research approach to the type of case study research. To explore data and information from informants, researchers used interviews, observations and study documents in the process of collecting research data. The conclusion of the study is that the perception of the community and parents about the quality of education is quite good, so with the planning and implementation of community participation and parents in general have done quite well. The impact that occurs is that the increasing community participation in the quality of education, the evaluation process has been carried out quite well even though found a little obstacle in the parents of new students who still need to be adjusted to the school program. The application in the field is known by the existence of community participation, it has an impact on the quality of education so that the increasing confidence of the community to send their children to school.Keywords: Participation, Education Quality.